Status, trends and prospects of development of Belarusian-Chinese cooperation in the face of increasing protectionism in international relations - Belski, Valery I.; Primschitz, Dmitry V.; Golubev, Sergei G.; Viartinskaya, Tatsiana S.; Berasneu, Dzmitry V.; Zaitseva, Ekaterina V. (Journal of the Belarusian State University. Economics, 2019)
The key aspects of the Belarusian-Chinese trust comprehensive strategic partnership and mutually beneficial cooperation are analyzed. Particular emphasis is placed on assessing the current state and identifying current trends in the implementation of political, trade-economic, credit-investment and interregional cooperation in the context of increasing protectionism in the world economy. It is emphasized that cooperation with the People’s Republic of China is one of the priority vectors of the foreign policy of the Republic of Belarus, and its further deepening fully meets the longterm national interests. The perspective directions and mechanisms of development of the bilateral relations focused on activation of interaction with the People’s Republic of China in the specified spheres for the purpose of strengthening of friendship and increase of welfare of the people of two countries are formulated.